Friedrich Nietzsche in Rene Girard’s Thought - Lozano, Pablo Ruiz (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
René Girard is an anthropologist, who has proposed an original hypothesis about the scapegoat mechanism and the relation between violence and religion. Starting from it he intends to work out a criticism of modernity, seeking out to recuperate the role of Christianity in the culture. From this perspective, he approaches the work of F. Nietzsche showing the two faces he finds out in the thinker: his intuition about the hidden truth of violence; and his rejection of this truth, to return to the violent origins of culture.
Keywords: scapegoat mechanism; Nietzsche; Christianity; violence; R. Girard.